Optimalisasi Ruang Terbuka Hijau dalam Mewujudkan Tata Ruang Kota yang Berkelanjutan - Djuarsa, Febby Firdian; Achmad, Mubarik; Labida, Lulu; Ernah, Ernah (Universitas Galuh, 2025)
Rapid urbanization and ecological pressures in urban areas demand more sustainable, inclusive, and adaptive city planning. Green Open Space (GOS) is seen as a strategic green infrastructure that not only functions ecologically as a microclimate balancer and provider of environmental services, but also plays a socio-cultural role as a public space that encourages social cohesion, expression of local identity, and improving the quality of life of city residents. This study reviews 30 national and international articles discussing GOS from five main sub-themes: policy and governance, spatial and design aspects, socio-cultural and ecological functions, roles in strengthening public space and social cohesion, and economic and ecological valuation. The results of the review show that various challenges are still faced in the implementation of GOS, ranging from weak integration of cross-sector policies, spatial inequality, to the lack of a participatory approach in planning. On the other hand, a number of studies also show the great potential of GOS as a means of mitigating climate change, a medium for citizen participation, and a symbol of the city's collective identity. Thus, the planning and management of GOS need to be carried out with a multidisciplinary approach, based on evidence, and in favor of social justice and ecological sustainability. Keywords: green open space, sustainable city, urban ecology, public space, social cohesion, ecological valuation.